Apakah Konsumen Impulsif dalam Membeli Makanan melalui Aplikasi Daring? Implikasi Promosi oleh Aplikasi Gojek, Emosi Positif, dan Minat Hedonis terhadap Pembelian Impulsif - Jean Richard Jokhu; Hannida Vena Charisma (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
The growth of digital technology in industry 4.0 provides convenience in all aspects of people's lives which causes the emergence of an easy and fast lifestyle. This condition encourages the fulfillment of daily needs through online media often occurs. Purchasing online makes it easier for consumers to make purchases of daily necessities such as food. The presence of hedonic motivation or intention and positive customer emotions can encourage spontaneous purchases. This study examines the effect of promotion on impulsive behavior in Gofood users. Using the SOR (Stimulus – Organisms – Response) model we introduced two intervening variables, positive emotion and hedonic intention, to mediate the relationship between promotion and impulsive behavior. This study uses SEM PLS (Structural Equation Modeling Partial Least Square) to explain the overall model in our study. A total of 325 respondents were collected in the Greater Jakarta area. Our research shows that promotion without positive emotions and hedonic intentions as a mediator will not affect the occurrence of impulsive behavior in Gofood users.